Pendampingan Implementasi Fun Learning Dalam Tahfidz Al-Qur’an Di Pondok Pesantren Wadil Qur’an - Latifah, Milahtul; Rahmawati Alwi; Robiatul Adawiyah (Institut Muslim Cendekia, 2025)
This article aims to describe the community service program of the Bogor Ummul Quro Al-Islamy Institute at the Wadil Qur'an Islamic Boarding School in Bogor. Where the service process focuses on assisting fun learning methods in memorizing the Qur'an. The fun learning method is applied in tahfidz Al-Qur'an to overcome the classic challenges in the memorization process that tend to be monotonous and boring, especially for children and adolescents. The main background of the application of this method is the need to foster intrinsic motivation, increase interest in learning, and create a more comfortable and pleasant atmosphere, so that students do not feel pressured during the memorization process. In addition, this approach also arises from the realization that the learning styles of students are very diverse, and adaptive and creative methods are needed to reach all students' characters. The method used in this study is qualitative research, the resource persons for this study consist of leaders, teachers and students of the Wadil Qur'an Islamic Boarding School, the data collection techniques that are carried out are observation and in-depth interviews. The data analysis technique carried out is descriptive analysis. The results of the study concluded that the application of fun learning in the process of memorizing the Qur'an at the Wadil Qur'an Islamic Boarding School proved to be effective in providing a conducive learning atmosphere so as to improve the quality of learning, and the quality of memorization of the Qur'an for students of the Wadil Qur'an Islamic Boarding School.